Development Of a Culinary Arts Textbook to Enhance the Competencies of Culinary Education Students - Febriani Lukitasari; Sri Handajani; Nugrahani Astuti; Hidayatun Muyasyaroh; Hanif Naufal Ahmi; Raida Amelia Ifadah; Anistian Nur Azizah (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
One of the most important factors in supporting the effectiveness of learning in higher education, especially in the field of culinary education. To assess its feasibility and effectiveness in improving the competence of students of the S1 Culinary Education Study Program, State University of Surabaya. This research uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The developed products were validated by material experts and media experts, while their effectiveness was tested through pre-test and post-test value analysis using the N-Gain test with a total of 30 students in the control class and 30 students in the experimental class. The results showed that material validation obtained a score of 91% with a very feasible category, while media validation obtained a score of 97% with a very feasible category. The results of the effectiveness test showed that the N-Gain value of the experimental class was 0.780 in the high category, while the control class obtained a value of 0.215 in the low category. These findings show that the Culinary Arts textbooks developed have an excellent level of feasibility and are effective in improving student understanding and competence. Thus, the development of this Culinary Arts textbook can be used as a supporting learning resource and support in improving the learning competence of culinary education students in higher education.